Framework for critical thinking skills as a preservice physics teacher competence - Misbah Misbah; Ida Hamidah; Siti Sriyati; Achmad Samsudin; Qamariah Qamariah; Nor Farahwahidah Abdul Rahman (Journal of Environment and Sustainability Education, 2025)
Critical thinking skills (CTS) are among the 21st-century skills needed. Preservice physics teachers need CTS to solve problems critically, not only in academics but also in life. This research offers a comprehensive perspective and understanding of critical thinking skills as a framework for measuring the ability of preservice physics teachers. The approach is qualitative with methodology analysis, and the documentary content produces a theoretical competence framework. Findings are then applied to determine CTS indicators' relevant competencies, such as clarity assumption, interpretation, analysis, reason, and evaluation. Preservice physics teachers can understand and use these results to evaluate CTS. The research emphasizes optimizing CTS for preservice physics teachers because education is increasingly complex and dynamic.